PENGARUH KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA PERAWAT: PERAN KECERDASAN EMOSIONAL SEBAGAI MEDIATOR - Wa Ode Zusnita Muizu; Andreas Recki Prasetyo; Yunizar Yunizar (PEKBIS, 2020)
Job satisfaction is an important element for nurses who are always working underpressure. This study aims to determine the effect of organizational commitment onjob satisfaction, as well as knowing the role of emotional intelligence as a mediatorof these two variables. This study was conducted on 106 nurses in the Banjar CityHospital. The research method used is verification. The hypothesis testing tool usedis path analysis, while for data processing using SPSS software. Hypothesis testingresults show there is no significant effect between organizational commitment to jobsatisfaction, and emotional intelligence mediate these two variables.